The Orang Asli in a Globalizing World: The Utilization of New Media in the Lives of Kintak - Zaheril Zainudin
The explosion of new media has made the exploration of academic research traditions gain more prominence in a globalizing world. The new media, as the hallmarks of communication processes, is unavoidable and has swept the Orang Asli communities, particularly Kintak in Malaysia, and the ocean of literature demands reviews on the issues of new media and Orang Asli. Thus, the purpose of this study is to examine the utilization of new media in the lives of Kintak. Further, this study embarks on the exploration of uses and gratifications of Islamic fundamentalism as a substratum in the context of communication and development, besides the intercultural context of hybridity, to investigate the needs and expectations of new media, besides types and levels of utilization, factors affecting and barriers to utilization. This qualitative case study using interviews and observation to collect the data from 13 informants includes Kintak and Non-Kintak in KOA Bukit Asu, Gerik Perak. The thematic analysis of the results indicates that there are myriads of needs and expectations for new media such as cognitive/surveillance/learning/information; affective/personal identity; personal integrative/personal relationships/personal identity; social integrative/integration and social interactions; and tensionfree/ diversion/entertainment/loneliness. The types and levels of utilization includes online newspaper (BH and HM); blogs (recipes and culture); social media platforms - audios (WA and YouTube), video (WA, FB and TikTok) and image sites (WA, FB and IG); websites - online shopping (Shopee and Lazada); virtual reality - nonimmersive VR (PlayerUnknown’s Battlegrounds (PUBG) and Candy Crush); wikis (Wikipedia); and vlogs (YouTube, IG and FB stories) at moderate level. The factor affecting utilization includes digitalization; accessibility/audience/user ability; convergence; virtuality/virtual communication/virtual relationships; interactivity; hybridity/cultural mixture; obsession/addiction; Islamization; and environment/family atmosphere. The barriers of utilization includes language barrier; semantic barrier/varying perception of reality; physical barrier/environmental/wrong choice of new media barrier; cultural/context barrier; socio-economic barrier; sociopsychological barrier; emotional/attention barrier; and physiological barrier. This study contributes a new and fresh review of literature on the utilization of new media, besides suggestions for improving utilization of new media in today’s globalizing digital world in the lives of Kintak.